Potential clinical usage of ashwagandha root extract: A review - Potocka, Zofia; Borycka, Aleksandra; Jędrzejewska, Barbara; Kotulska, Maria; Laskus, Paulina; Lichman, Martyna; Lubczyńska, Zuzanna; Przeradzki, Jakub; Rząd, Katarzyna (Journal of Education, Health and Sport, 2023)
INTRODUCTION AND OBJECTIVE Ashwagandha, an herb commonly used in traditional Indian medicine, has been gathering attention as a potential drug in various specialties such as psychiatry, neurology, or endocrinology and even as a possible cancer treatment. In this review we aim to summarize reports form recent years on potential clinical usage of Ashwagandha. REVIEW METHODS The literature review was conducted using PubMed and Google Scholar online databases. THE STATE OF KNOWLEDGE Several studies evaluating potential pharmacological uses of Ashwagandha root extract has been published. There are clinical trials conducted in India using the plant in treatment of insomnia that resulted in improved sleep quality. Ashwagandha root extract has been successfully administered in stress-related disorders. There are reports of improvement in cognitive functions in patients with mild cognitive impairment and better symptom control in obsessive-compulsive disorder after Ashwagandha supplementation. Ashwagandha has been studied in endocrine diseases, showing potential in alleviating climacteric symptoms during perimenopause and in subclinical hypothyroidism. The study aimed to assess effect of Ashwagandha on vitality and hormonal changes in elderly men showed mixed results, with improvement in some hormonal levels and not statistically significant improvement in quality of life compared to placebo group. It has also been noted that ashwagandha root extract has positive effect on cardiovascular system, as well as enhancing muscle strength and recovery in otherwise healthy adults. SUMMARY Ashwagandha root extract seems to possess beneficial properties that allow for its use in several branches of medicine. However as current findings are reported from small sample studies, further research on a larger scale is needed.